Current trends in multidrug-resistant AmpC beta-lactamase producing Enterobacter cloacae isolated from a tertiary care hospital (Bangladesh Journal of Medical Science, 2020)
Background: The emergence of AmpC beta-lactamase producing Enterobacter cloacae becomes a serious nosocomial menace due to wider resistance. The study aimed to know the existence of these superbugs in the hospital settings and to report the current trends in their antibiotic resistance.Methods: We chose a tertiary care pediatric hospital for this cross-sectional study and processed 27,000 clinical specimens for the isolation of E. cloacae using routine microbiological procedures. A total number of 96 E. cloacae isolates from various sources were screened for AmpC production with cefoxitin (30 μg) and confirmed by inhibitor based technique. The antibacterial drug resistance studied against various groups of antibiotics in vitro.Results : Boronic acid inhibitor based method revealed 63 (65.6%) pathogens as AmpC beta-lactamase producing E. cloacae. Most of the infected patients with AmpC producing E. cloacae were neonates (34; 54.0%) and infants (11; 17.5%). The primary source of AmpC producing E. cloacae was blood (43; 68.3%), and they were frequently distributed in the neonatal nursery unit (33; 52.4%) and medical ward (13; 20.6%). All of these bugs showed a high level of resistance (100%) against the co-amoxiclav and cephalosporin group.The organisms exhibited less resistance to levofloxacin, imipenem and colistin sulphate as 23 (36.5%), 20 (31.7%) and 17 (27.0%), respectively.Conclusion: The consistent emerging threat of Amp C harbouring E. cloacae could disseminate AmpC genes in other genera of the bacteria which lead to the therapeutic failure and leave the doctors with limited treatment options of levofloxacin, imipenem and colistin sulphate.Bangladesh Journal of Medical Science Vol.19(4) 2020 p.632-637